Experimental Assessment Of The Breaking Strength Of Tross Used In The Management Systems Of Reduced Vehicles (Texas Journal of Engineering and Technology, 2025)
This article analyzes the reliability of modernized vehicles for people with disabilities and the cables used in them. Steel cables used in mechanical control devices for people with disabilities were investigated. During the research, international and national standards were analyzed, and a methodology for determining the compliance of cables used in manual control systems with established requirements was developed. New technological approaches to testing cables for elongation and tear during the conversion of vehicle foot pedals to manual control are also being considered. The article's results are aimed at testing the ability of people with disabilities to withstand the loads that arise when using vehicles, as well as developing a justification for prohibiting or prohibiting their use and offering solutions